Interactions Required for Binding of Simian Virus 40 T Antigen to the Viral Origin and Molecular Modeling of Initial Assembly Events - Reese, Danielle K. (American Society for Microbiology, 2004)
The purified T-antigen origin binding domain binds site specifically to site II, the central region of the simian virus 40 core origin. However, in the context of full-length T antigen, the origin binding domain interacts poorly with DNA molecules containing just site II. Here we investigate the contributions of additional core origin regions, termed the flanking sequences, to origin recognition and the assembly of T-antigen hexamers and double hexamers. Results from these studies indicate that in addition to site-specific binding of the T-antigen origin binding domain to site II, T-antigen assembly requires non-sequence-specific interactions between a basic finger in the helicase domain and particular flanking sequences. Related studies demonstrate that the assembly of individual hexamers is coupled to the distortions in the proximal flanking sequence. In addition, the point in the double-hexamer assembly process that is regulated by phosphorylation of threonine 124, the sole posttranslational modification required for initiation of DNA replication, was further analyzed. Finally, T-antigen structural information is used to model various stages of T-antigen assembly on the core origin and the regulation of this process.